How to Classify Clinical Trials Using the PEDro Scale? - Matos, Areolino Pena; Pegorari, Maycon Sousa (Journal of Lasers in Medical Sciences, 2020)
Letter to editor regarding to article "The Effects of Photobiomodulation Therapy on Post-Surgical Pain", Kamran Ezzati, Reza Fekrazad, Zeinab Raoufi. J Lasers Med Sci 2019 Spring;10(2):79-85